Bioanalytical LC–MS/MS validation of therapeutic drug monitoring assays in oncology. (27th November 2019) - van Nuland, Merel; Rosing, Hilde; Schellens, Jan H.M.; Beijnen, Jos H.
Abstract: Therapeutic drug monitoring (TDM) has shown to benefit patients treated with drugs of many drug classes, among which is oncology. With an increasing demand for drug monitoring, new assays have to be developed and validated. Guidelines for bioanalytical validation issued by the European Medicines Agency and US Food and Drug Administration are applicable for clinical trials and toxicokinetic studies and demand fully validated bioanalytical methods to yield reliable results. However, for TDM assays a limited validation approach is suggested based on the intended use of these methods. This review presents an overview of publications that describe method validation of assays specifically designed for TDM. In addition to evaluating current practice, we provide recommendations that could serve as a guide for future validations of TDM assays.